Analysis of Transmigration Program Impact on Community Economic Improvement in Discrete Aimas Sorong Regency - Abubakar, Endang; La Ibal; Murni (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Through the transmigration program, it is hoped that mutually beneficial cooperation will be created between the transmigrant community and local communities around the transmigration settlement locations. The aim of this research is to analyze the impact of the transmigration program on improving the community economy in the Aimas District, Sorong Regency. This research uses quantitative research methods. Data analysis in this research is a normality test, reliability and validity test, and simple regression analysis. The research results show that the influence of transmigrants is 77.4% on improving the community's economy, while 23.6% is influenced by other factors not examined in this research. The Transmigrant variable has a positive effect on economic improvement. The regression coefficient value for the Transmigrant variable is 0.100, which indicates that the Transmigrant variable has a positive effect on economic improvement. Through simple linear regression analysis, it turns out that the relationship that occurs is a positive influence relationship. Through analysis of the coefficient of determination, it turns out that transmigration has an effect of 59.9% because transmigration has a good effect on the socio-economic life of the community in the Aimas District, Sorong Regency. It can be concluded that the community's economy can be improved through the transmigration program.